Objek Wisata Kali Biru (Lakaranda) Di Desa Mosolo Kabupaten Konawe Kepulauan Dengan Penekanan Arsitektur Berkelanjutan - Ahyarky Abidin, Afri; Sari Taufiq, Elvina; Nahdatunnisa, Nahdatunnisa; Mirwanto, Mirwanto (Architectura : Journal of Architecture and Planning, 2025)
The development of marine tourism in all regions of Indonesia, the Konawe Islands regency is one of the provinces in Indonesia that has potential in the development of marine tourism. Purpose of designing a tourist attraction Kali Biru (Lakaranda) Mosolo the most important thing in planning is to design a site to support all activities and be able to accommodate the function of the building. The design results show that the Kali Biru (Lakaranda) tourist area needs to be reviewed in developing supporting facilities and main facilities for visitors to fulfill activities in traveling activities, using sustainable architectural design principles where architectural design considers environmental, social and economic impacts.